(untitled) (Research, Society and Development, 2021)
In Amazon region is located one of the largest reserves of fresh water in the world, where there is often the paradox that in many riverside cities, the population is not provided with treated and quality water. The Solimões River is one of the largest rivers today, where many people reside along its passage. The objective of this work was to evaluate the coagulant action of three commercial products (Aluminum Sulfate, Ferric Chloride and Polyaluminium Chloride) for use in the Water Treatment Plant of Careiro da Várzea. The methodology was divided into three stages, starting with the monitoring of physico-chemical and bacteriological analyzes of the water source at the water catchment site. Then, bench tests were carried out using Jar Test with concentrations from 7 to 25 ppm, for each coagulant, to verify the optimal characteristics of the process. Finally, the tests were carried out at the city’s WTP for 24 hours and the parameters of turbidity and color were monitored. The results showed that the source presented basic characteristics, with high turbidity and color. In laboratory tests, as well as in the scale-up, it was found that the commercial coagulant, ferric chloride, presented better efficiency at 20 ppm with WTP operating conditions of 0.2 ppm flocculant and pH 7.